On Usain Bolt's running mechanics - Richmond, J. (New Studies in Athletics, 2017)
Usain Bolt (JAM) is the greatest male sprinter the world has seen. Examination of his running technique reveals biomechanical features that are significantly different from other contemporary sprinters. These could be part of the explanation for his ability and success and are therefore of interest to aspiring athletes, their coaches and fans. Using freely available video material and simple tools, the author studied the support phase of the stride cycle and found that Bolt flexes his knee through the phase much like other top sprinters but, unlike most, he then extends the knee prior to the toe-off of each stride. Bolt also extends his lower torso (lumbar spine) during the propulsion phase, which when combined with the knee extension allows him to use a longer leg lever and increase his ground contact time. More importantly, the manner in which he incorporates the lumbar extension allows the involved muscles to operate within a range of movement that facilitates optimal length-tension relationships, thereby increasing the amount of force they can generate. Ultimately this produces greater force against the ground for a longer time, increasing the impulse and therefore the running velocity.